Meta-Analysis on the Effects of Family- Oriented Prevention in German-Speaking Countries: A Contribution to Cross-Cultural Generalization - Weiss, Maren; Schmucker, Martin; Lösel, Friedrich (International Journal of Developmental Science, 2022)
Most research on developmental prevention programs stems from Anglo-American countries. However, in German-speaking European countries, there is also a broad range of family-oriented programs to promote child development and prevent behavioral problems. This article presents a meta-analysis of n = 79 studies on family-based prevention that had a comparison group and were performed in Germany, Austria, or Switzerland. Overall, the data contained 10,667 parents and showed a significant positive mean effect of the programs (d = 0.31). The mean effect for parent related outcomes (d = 0.40) was larger than for measures of child behavior (d = 0.20). There was much heterogeneity across studies and very few had follow-ups of more than one year. Moderator analyses revealed particular influences of methodological study characteristics, e.g. larger effects in smaller samples and less well-controlled studies. Most results of our meta-analysis are similar to what has been found in the English-speaking world. However, as in international practice, the evaluated programs seem to be not representative for everyday prevention reality where many programs are not evaluated at all. Our study confirms the need for more high-quality and long-term evaluation as well as cross-national comparisons and replicated moderator analyses.<br
Keywords: Family-based prevention; parent training; outcome evaluation; meta-analysis; cross-cultural generalization